3v+6v-3(4v-2v)=

Simple and best practice solution for 3v+6v-3(4v-2v)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3v+6v-3(4v-2v)= equation:


Simplifying
3v + 6v + -3(4v + -2v) = 0

Combine like terms: 4v + -2v = 2v
3v + 6v + -3(2v) = 0

Remove parenthesis around (2v)
3v + 6v + -3 * 2v = 0

Multiply -3 * 2
3v + 6v + -6v = 0

Combine like terms: 3v + 6v = 9v
9v + -6v = 0

Combine like terms: 9v + -6v = 3v
3v = 0

Solving
3v = 0

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Divide each side by '3'.
v = 0

Simplifying
v = 0

See similar equations:

| (1-z)(5z-6)=0 | | -.5x=8 | | 50=5/9(f-32) | | .80x=5780 | | 5(-1)-7(-3)= | | 6(p+q)= | | 11t+9t=20 | | 0.17x+0.04(x+3000)=1170 | | -4(-x-16)=-4x-16 | | 3.5d=70d | | N+23=92 | | 20=x/4-2 | | 9y-15= | | 8a-7a=5 | | =6(-6)+30 | | f(.04)=9ln | | sqrt(3x+10)-2=5 | | -0.10(34)+0.25x=0.05(x-12) | | =6(-5)+30 | | 10*n=110 | | 15=02z | | 7y-15= | | 22+2q=37+6+q | | 1.2=0.2k | | (x*.20)+x=5780 | | =6(-1)+30 | | -log(x)=8.42 | | 0.75x+0.05(16-x)=0.10(-62) | | d^2+d-400=0 | | -2x+3=19+6x | | 5m=0.95 | | u^5-13u^2+36=0 |

Equations solver categories